2013
DOI: 10.1371/journal.pone.0053825
|View full text |Cite
|
Sign up to set email alerts
|

Does Wheat Genetically Modified for Disease Resistance Affect Root-Colonizing Pseudomonads and Arbuscular Mycorrhizal Fungi?

Abstract: This study aimed to evaluate the impact of genetically modified (GM) wheat with introduced pm3b mildew resistance transgene, on two types of root-colonizing microorganisms, namely pseudomonads and arbuscular mycorrhizal fungi (AMF). Our investigations were carried out in field trials over three field seasons and at two locations. Serial dilution in selective King's B medium and microscopy were used to assess the abundance of cultivable pseudomonads and AMF, respectively. We developed a denaturing gradient gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…In our case, however, the wheat plants carrying Pm3b and Chi and Glu transgenes did not seem to change the post-harvest vegetation, at least within the 6-month time period. Our findings correspond to the results of several companion studies which showed no effects of these particular GM plants on non-target organisms, such as insect species (Alvarez-Alfageme et al, 2011;Peter et al, 2010;von Burg et al, 2010), soil fauna (Duc et al, 2011) or soil beneficial bacteria and mycorrhizal fungi (Meyer et al, 2013;Song Wilson et al, 2010).…”
Section: Post-harvest Weed Vegetationsupporting
confidence: 90%
“…In our case, however, the wheat plants carrying Pm3b and Chi and Glu transgenes did not seem to change the post-harvest vegetation, at least within the 6-month time period. Our findings correspond to the results of several companion studies which showed no effects of these particular GM plants on non-target organisms, such as insect species (Alvarez-Alfageme et al, 2011;Peter et al, 2010;von Burg et al, 2010), soil fauna (Duc et al, 2011) or soil beneficial bacteria and mycorrhizal fungi (Meyer et al, 2013;Song Wilson et al, 2010).…”
Section: Post-harvest Weed Vegetationsupporting
confidence: 90%
“…Differences in AMF root colonisation and Pseudomonas population dynamics were observed among wheat plants expressing the pm3b mildew resistance transgene and parental lines. Conversely, no differences were detected between GM and non-GM sister lines, obtained through the same tissue culture and regeneration process, demonstrating that the differences in root colonisation may be ascribed to the transformation technology [51].…”
Section: Transgenic Plants Resistant To Phytopathogenic Bacteria and mentioning
confidence: 84%
“…Other studies have not found any significant differences in rhizosphere microbiomes between wild-type maize and maize genetically engineered to produce Bacillus thuringiensis (Bt) toxin [100,101], although this may be due to Bt toxin being insecticidal rather than antibacterial. Also, in the wheat rhizosphere, introduction of the pm3b gene conferring resistance to mildew had minimal effect on pseudomonads and mycorrhizal fungi populations [102]. Disease resistance, including production of antimicrobial compounds, is a trait likely to be introduced as a result of molecular breeding or genetic modification in attempts to control diseases.…”
Section: The Effect Of the Host On The Plant Microbiomementioning
confidence: 99%